Dysregulation of CDK Inhibitors and p53 in HPV-negative Endocervical Adenocarcinoma. (March 2015) - Omori, Makiko; Hashi, Akihiko; Kondo, Tetsuo; Katoh, Ryohei; Hirata, Shuji
<x xml:space="preserve">Abstract</x> Human papillomavirus (HPV)-negative adenocarcinoma (AC) is a minor subset of endocervical cancer, but its pathogenesis has yet to be elucidated. This study investigated the clinicopathologic features of HPV-negative endocervical AC (n=14) in comparison with HPV-positive endocervical AC (n=30), and further studied aberrations of cell-cycle regulators. Expression patterns of cyclin-dependent kinase inhibitors (p16, p14, p27, and p21) and p53 were evaluated immunohistochemically, and nuclear high-risk HPV DNA signals were detected by in situ hybridization and polymerase chain reaction. Immunoexpression of p16, p14, p27, p21, and p53 were observed in 90%, 67%, 77%, 40%, and 20% of HPV-positive ACs, and in 0%, 0%, 29%, 14%, and 57% of HPV-negative ACs, respectively. A higher frequency of lymph node metastasis and worse prognosis were significantly associated with HPV-negative AC. Our findings suggest that alteration of cyclin-dependent kinase inhibitors and p53 status may contribute to carcinogenesis and the clinical behavior of HPV-negative AC of the uterine cervix.